ANALISIS MIKROBIOLOGI Escherichia coli JAJANAN MINUMAN DI SEKITAR JALAN KAPTEN MUSLIM KOTA MEDAN - Siti Maimunah; Artha Yuliana Sianipar; Cut Masyithah Thaib (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Escherichia coli is a gram-negative rod bacteria, not encapsulated and is a normal flora in the digestive tract of animals and humans that easily pollutes water. Escherichia coli can turn into an opportunist pathogen if it lives outside the intestine, for example in urinary tract infections, wound infections and mastitis. Drinks contaminated with microorganisms can cause health problems in the form of disturbances in the digestive tract with symptoms of nausea, heartburn, vomiting and diarrhea. The purpose of this study was to determine the presence of Escherichia coli bacterial contamination in snacks sold around the Kapten Muslimstreet. This descriptive study used 4 samples of iced drinks, namely young coconut ice, sugar cane ice, mixed ice and dawet ice. The sample testing technique uses the Most Probable Number (MPN) method. The media used in this study were lactose Broth, Brilliant Green Lactose Bile Broth, Eosin Methylene Blue Agar. This research was conducted at the Pharmacy Microbiology Laboratory, Sari Mutiara University, Indonesia. After the research, the results showed that 1 of 4 samples of snacks found on Jalan Captain Muslim was detected with Escherichia coli bacteria ranging from 2,800 cells/100 ml so that it was included in the poor criteria, in the category These snacks are not suitable for consumption and do not meet the criteria set out in the Indonesian Ministry of Health No.492/Menkes/Per/IV/2010 (Colifrom and Escherichia coli 0/100 ml).